Sustainability mindset as antecedent of intention to work in sustainable maritime transportation company amongst Filipino seafarers - Dui, Rayan P. (Animo Repository, 2022)
There are limited studies on what factors drive and influence the decision of seafarers to work for a particular maritime organization. This dissertation focused on determining the factors that may motivate their intention to work for these sustainable maritime organizations grounded on the Theory of Planned Behavior. An extension of this approach was used in identifying the anteceding role of the sustainability mindset and its elements in influencing the determinants of behavioral intention with the inclusion of perceived gender equality. This research was anchored on the Positivist philosophy, where the focus is to observe the regularity of a particular phenomenon, look for causal relationships, and support them with statistical evidence to create a generalization. The research design used in this study was quantitative descriptive and explanatory. Descriptive since the study described the nature of sustainability mindset through its elements and its anteceding role in influencing seafarers’ intention to work in sustainable maritime transportation. It was explanatory since it described the relationship among the variables included in the framework. A survey of 469 seafarer respondents was conducted utilizing PLS-SEM as a statistical tool to analyze the relationships of the latent variables in the structural framework. The results suggest that the seafarers’ perceived behavioral control p-value < 0.001, with 95% CI [0.205, 0.500], has a significant and positive relationship with their behavioral intention of working for sustainable maritime transportation companies. Likewise, based on the findings, indicators imply that the emotional intelligence element of the sustainability mindset p-value < 0.001, with 95% CI [0.511, 0.734], was the primary catalyst in influencing the seafarer’s perceived behavioral control. The spiritual intelligence element of the sustainability mindset p-value = 0.018, with 95% CI [0.023, 0.268], also partially stimulated the seafarers' perceived behavioral control. Determinants of this behavioral intention and antecedents of these predictors may expose areas for possible interventions in improving Filipino seafarers’ interest in addressing sustainability challenges, particularly on issues in the maritime transportation sector's economic, environmental, and social dimensions. The findings of this study may also provide valuable insights to vital maritime stakeholders on how they may tailor their programs designed to influence and motivate seafarers to work for a sustainable maritime organization. The overarching result of this study suggests that those individuals who exhibit emotional intelligence and spiritual intelligence, both elements of a sustainability mindset, are more motivated to perform sustainable related activities and can better inspire people to find true meaning in their work.